Effect of O2 on the adsorption of SO2 on carbon-supported pt electrocatalysts - K. Punyawudho (2018)
Adsorption of SO2 in the presence of O2 on Pt/C catalysts often used as electrocatalysts has been investigated by temperature programmed desorption (TPD) and X-ray photoelectron spectroscopy (XPS). The amounts of SO2 adsorption on Pt/C in the presence of O2 were much higher than those in the absence of O2 (SO 2-N2) and from the carbon support (Vulcan XC-72) alone. Adsorption is dependent on oxygen concentration over the range 0-20% but reaches saturation at 20% O2. The spillover of SO2 from Pt to the carbon support has been proposed for 10, 20, and 40% Pt loadings, characterized by desorption temperatures of approximately 150 and 260 °C for SO 2 adsorbed on Pt and carbon, respectively. Adsorbed Pt-S, C-S, C-SOx, and Pt-SO4 species were identified by XPS as S-containing species on both Pt and carbon. Both TPD and XPS indicate that the carbon support plays a major role in SO2 adsorption, primarily as SOx (x = 3, 4). The bonding of S and SOx on the carbon support was strong enough that back diffusion to the Pt surface did not occur. © 2011 American Chemical Society.